2011
DOI: 10.1007/s10165-011-0468-x
|View full text |Cite
|
Sign up to set email alerts
|

Serum adipokine profiles in Kawasaki disease

Abstract: Adipokines are cytokines derived from adipose tissue. Recently it has been established that adipokines are closely linked to the pathophysiology of not only metabolic diseases, such as diabetes mellitus, obesity, and atherosclerosis, but also to inflammation and immune diseases. In this study we measured serum levels of adipokines in patients with acute Kawasaki disease to investigate the role of adipokines in the pathophysiology of Kawasaki disease. Serum resistin, high-molecular-weight (HMW) adiponectin, lep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
(34 reference statements)
2
6
0
Order By: Relevance
“…Our finding of the increased levels of resistin from KD patients is in agreement with the previous research in Japanese patients with KD [33]. In a recent study, the results suggest that high serum resistin level may be a predictor of nonresponsiveness to intravenous immune globulin therapy [34]. However, there were no obvious differences in the genomic frequencies and genotype between responders and nonresponders Therefore, more studies are needed to confirm the hypothesis that the association between resistin concentration and the nonresponders.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding of the increased levels of resistin from KD patients is in agreement with the previous research in Japanese patients with KD [33]. In a recent study, the results suggest that high serum resistin level may be a predictor of nonresponsiveness to intravenous immune globulin therapy [34]. However, there were no obvious differences in the genomic frequencies and genotype between responders and nonresponders Therefore, more studies are needed to confirm the hypothesis that the association between resistin concentration and the nonresponders.…”
Section: Discussionsupporting
confidence: 92%
“…Yoshino et al [57] reported that the plasma levels of resistin and leptin positively correlated with the CRP level in patients with rheumatoid arthritis. Similar observations in patients with Kawasaki disease come from Kemmotsu et al report [67]. The level of CRP was significantly associated with an increased level of resistin in that study.…”
Section: Discussionsupporting
confidence: 90%
“…In fact, studies conducted in other forms of vasculitis, such as Kawasaki disease 35 and Behçet disease 36 , showed higher resistin levels than healthy controls but no differences in adiponectin levels. In fact, studies conducted in other forms of vasculitis, such as Kawasaki disease 35 and Behçet disease 36 , showed higher resistin levels than healthy controls but no differences in adiponectin levels.…”
Section: Rheumatologymentioning
confidence: 93%